Designing Gabor filter for fingerprint recognition using Verilog HDL / Abdul Hadi Abdul Razak, Adizul Ahmad and Mohd Faizul Md Idros - Abdul Razak, Abdul Hadi; Ahmad, Adizul; Md Idros, Mohd Faizul (2009)
This paper presented the implementations of Gabor filter for fingerprint recognition using Verilog HDL. This work demonstrated the application of Gabor Filter technique to enhance the fingerprint image. The incoming signal in form of image pixel will be filter out or convolute by the Gabor filter to define the ridge and valley regions of fingerprint. This was done with the application of a real time convolve based on Field Programmable Gate Array (FPGA) to perform the convolution operation. The main characteristic of the proposed approach were the usage of memory to store the incoming image pixel and the coefficient of the Gabor filter before the convolution matrix take place. This FPGA filter can be categories as reconfigurable filter as the characteristic of the Gabor filter can be change by changing the coefficient stored in the memory.